THE EXPLORING STUDENTS’ CHALLENGES IN USING ROBLOX FOR NARRATIVE WRITING - Cahyani Dwiputri; Irsyad Nugraha; Sinta Dewi (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
This article explores the challenges experienced by ninth-grade EFL students when Roblox was used as an experiential prompt for narrative writing. The study was conducted in an Indonesian junior high school classroom through a qualitative case study design. Data were drawn from four teacher-researcher observation field notes and three semi-structured interviews with focal students coded as S1, S2, and S3. The learning sequence followed four stages: Building Knowledge of the Field, Modeling of the Text, Joint Construction of the Text, and Independent Construction of the Text. Thematic analysis revealed that Roblox provided vivid ideas, settings, characters, conflicts, and chronological events, but it did not automatically lead to coherent English narrative writing. Five major challenges emerged: technical and access barriers, difficulty transforming gameplay into English sentences, difficulty selecting and organizing narrative elements, tension between engagement and distraction, and different levels of student independence. The findings suggest that Roblox can support narrative writing when it is combined with clear genre-based scaffolding, guided worksheets, vocabulary and past-tense support, immediate post-game writing activities, and equitable technical preparation. Thus, the main pedagogical issue is not whether students enjoy Roblox, but how teachers help them transform game experiences into organized and linguistically accurate narrative texts. ABSTRAK Artikel ini mengeksplorasi tantangan yang dialami siswa EFL kelas IX ketika Roblox digunakan sebagai prompt pengalaman untuk menulis teks naratif. Penelitian dilakukan di salah satu kelas sekolah menengah pertama di Indonesia dengan desain studi kasus kualitatif. Data diperoleh dari empat catatan observasi guru-peneliti dan tiga wawancara semi-terstruktur dengan siswa fokus yang dikodekan sebagai S1, S2, dan S3. Rangkaian pembelajaran mengikuti empat tahap, yaitu Building Knowledge of the Field, Modeling of the Text, Joint Construction of the Text, dan Independent Construction of the Text. Analisis tematik menunjukkan bahwa Roblox membantu siswa memperoleh ide, latar, tokoh, konflik, dan urutan peristiwa yang konkret, tetapi pengalaman bermain tidak secara otomatis menghasilkan tulisan naratif berbahasa Inggris yang runtut dan akurat. Lima tantangan utama ditemukan, yaitu hambatan teknis dan akses, kesulitan mengubah pengalaman bermain menjadi kalimat bahasa Inggris, kesulitan memilih dan mengorganisasi unsur naratif, ketegangan antara keterlibatan dan distraksi, serta perbedaan tingkat kemandirian siswa. Temuan ini menunjukkan bahwa Roblox dapat mendukung pembelajaran menulis naratif apabila dipadukan dengan scaffolding berbasis genre, LKPD terarah, dukungan kosakata dan simple past tense, kegiatan menulis segera setelah bermain, serta persiapan teknis yang adil bagi siswa.